Surface-enhanced transmission polyvinyl alcohol-based hydrogel and preparation method thereof

By preparing polyvinyl alcohol-based hydrogels with three-dimensional network porous structure and surface reaming structure, the problems of excessive adhesion time of polyvinyl alcohol-based hydrogels and insufficient drug release ability are solved, and efficient drug delivery and healing effects are achieved.

CN119684667AActive Publication Date: 2025-03-25PLASTIC SURGERY HOSPITAL CHINESE ACADEMY OF MEDICAL SCIENCES +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411875935.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-25
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing polyvinyl alcohol-based hydrogel adheres for too long when adhering to the wound, causing the temperature of the wound to rise and increase the risk of infection. At the same time, its drug release ability is insufficient, affecting the healing effect.

Method used

By configuring the polyvinyl alcohol solution and sodium alginate, circulating freezing-thaw cross-linking treatment, and soaking in the ammonium sulfate-borax solution, a polyvinyl alcohol-based hydrogel with a three-dimensional network porous structure and a surface porous structure were prepared.

Benefits of technology

The hydrogel has excellent mechanical properties, drug release ability and adhesion stability, and can quickly deliver drugs to the wound, thereby promoting wound healing. At the same time, due to the presence of the reaming structure, the contact between the hydrogel and the wound surface is enhanced and the adhesion performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684667A_ABST
    Figure CN119684667A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following preparation steps: preparing a polyvinyl alcohol solution, adding sodium alginate into the polyvinyl alcohol solution, stirring to enable the sodium alginate to be completely dissolved in the polyvinyl alcohol solution to prepare a mixed solution, putting the mixed solution into a mold for pre-gelatinization, and then carrying out surface-enhanced transport on the surface of the polyvinyl alcohol-based hydrogel to obtain the surface-enhanced transport polyvinyl alcohol-based hydrogel. The preparation method comprises the following steps: performing cyclic freezing-melting cross-linking treatment, and then soaking in an ammonium sulfate-borax solution to finally prepare the polyvinyl alcohol-based hydrogel, a three-dimensional network porous structure is formed in the polyvinyl alcohol-based hydrogel, the pore diameter of the porous structure is 200nm-8mu m, and a pore expanding structure capable of enhancing transmission is formed on the surface of the polyvinyl alcohol-based hydrogel. The pore diameter of the pore expanding structure is 10-150 [mu] m, and the pore expanding structure is communicated with the porous structure. The surface enhanced transmission polyvinyl alcohol-based hydrogel provided by the invention has excellent ionic conductivity, drug release ability, mechanical property and adhesion property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of preparation of polyvinyl alcohol-based multifunctional hydrogels, in particular to a surface enhanced transmission polyvinyl alcohol-based hydrogel and a preparation method thereof. Background Art

[0002] Hydrogel is a polymer material system with a three-dimensional network structure formed by cross-linking hydrophilic polymer chains. It has good water storage and moisture retention capacity, material exchange capacity and properties similar to those of the extracellular matrix. It has been widely used in the fields of drug delivery and release, tissue repair, medical excipients and tissue engineering. Among them, polyvinyl alcohol (PVA) has good film-forming properties, mechanical properties, degradability and safety, and is one of the most widely used raw materials for biomedical hydrogels. Traditional gauze soaked in liquid medicine needs to be fixed with the help of bandages, and the drug will be released quickly and flow to other parts of the body, resulting in the inability to fully exert the drug effect. In comparison, polyvinyl alcohol-based hydrogels can be effectively attached to the wound, not easy to fall off, and have the function of sustained release of drugs. It can continuously promote wound healing with the sustained release of drugs and give full play to the effect of drugs. However, when applying wounds such as scalds and burns, the adhesion time of polyvinyl alcohol-based hydrogels is too long, which easily causes the temperature of the wound site to rise and increases the risk of infection. Therefore, how to regulate the drug sustained release ability of polyvinyl alcohol-based hydrogels so that they can complete drug delivery and release within an appropriate time is a research with great application value in the field of biomedicine.

[0003] At present, in order to better improve the sustained release ability of polyvinyl alcohol-based hydrogels, the method of forming macroporous polyvinyl alcohol hydrogels is mainly used to improve the drug delivery ability. The Chinese patent application with application number 201810356499.8 discloses a method for preparing a sponge-like macroporous polyvinyl alcohol hydrogel. After dissolving polyethylene glycol in a polyvinyl alcohol solution, the mixed solution is phase separated by lowering the temperature, and then nano-hydroxyapatite is added to the mixed solution that has undergone phase separation to stabilize the phase separation system. The hydrogel is formed by a cyclic freezing / melting method, and the polyethylene glycol and nano-hydroxyapatite are washed out to obtain a polyvinyl alcohol hydrogel with a pore size of 30 to 100 μm, which has a sponge-like appearance, elasticity, and a three-dimensional porous structure. Since the macroporous structure is a structural defect for the material, the macroporous structure is more likely to cause material failure under the action of external forces. The Chinese patent application with application number 202310030838.4 discloses a super-macroporous hydrogel and its preparation method and application, which is formed by cross-linking sodium alginate and polyvinyl alcohol under calcium chloride as a cross-linking agent, and a super-macroporous sodium alginate hydrogel with high porosity (~85%) and large pore size (100 microns to 900 microns) is obtained, and at the same time, excellent mechanical properties are obtained. However, due to the penetration of calcium ions from the outside to the inside for cross-linking, the pore size of the formed macropores is distributed in a gradient manner from large to small inside. The closer to the surface position, the smaller the pore size, which is not conducive to the transportation of drugs inside the hydrogel to the surface to the wound site for release. Therefore, how to improve the drug release capacity of the multifunctional hydrogel and have good mechanical properties and adhesion properties to meet the application needs of biomedical hydrogels is of great significance. Summary of the invention

[0004] The purpose of the present invention is to provide a surface enhanced transmission polyvinyl alcohol-based hydrogel and a preparation method, which can improve the drug release ability of the hydrogel and have good mechanical properties and adhesion properties.

[0005] In a first aspect, the present invention provides a method for preparing a surface enhanced transport polyvinyl alcohol-based hydrogel, comprising the following preparation steps: preparing a polyvinyl alcohol solution, adding sodium alginate to the polyvinyl alcohol solution, stirring to completely dissolve the sodium alginate in the polyvinyl alcohol solution, preparing a mixed solution, placing the mixed solution in a mold for pre-gelation, and then performing a cyclic freeze-thaw cross-linking treatment. After completion, placing the mixed solution in an ammonium sulfate-borax solution for immersion treatment, and finally preparing a polyvinyl alcohol-based hydrogel, wherein a three-dimensional network porous structure is formed inside the polyvinyl alcohol-based hydrogel, and the pore size of the porous structure is 200nm~8μm, and a pore expansion structure capable of enhancing transport is formed on the surface of the polyvinyl alcohol-based hydrogel, and the pore size of the pore expansion structure is 10μm~150μm, and the pore expansion structure is connected to the porous structure.

[0006] Optionally, the pore size of the porous structure is 500 nm to 8 μm; the pore size of the expanded pore structure is 10 μm to 150 μm.

[0007] Optionally, the pore size of the porous structure is 600 nm to 8 μm; the pore size of the expanded pore structure is 25 μm to 150 μm.

[0008] Optionally, a polyvinyl alcohol solution is prepared, comprising:

[0009] The polyvinyl alcohol is added into deionized water, the mass ratio of the polyvinyl alcohol to deionized water is 5-15:45-180, and the polyvinyl alcohol is completely dissolved in the deionized water by stirring at 50-95° C., so as to prepare the polyvinyl alcohol solution, and the stirring speed is 50-500 rpm / min.

[0010] Optionally, sodium alginate is added to the polyvinyl alcohol solution and stirred to completely dissolve the sodium alginate in the polyvinyl alcohol solution to prepare a mixed solution, comprising:

[0011] The sodium alginate is added to the polyvinyl alcohol solution, the mass ratio of the sodium alginate to the polyvinyl alcohol solution is 2-8:45-180, and the mixture is stirred at 50-95° C. and the stirring speed is 50-500 rpm / min to prepare the mixed solution.

[0012] Optionally, placing the mixed solution in a mold for pre-gelling comprises:

[0013] The mixed solution is placed in a mold and allowed to stand for 0.5 to 5 hours.

[0014] Optionally, a cyclic freeze-thaw crosslinking treatment is performed, including:

[0015] The freezing-thawing process is performed for 2 to 6 cycles, wherein the freezing temperature is -90°C to -60°C, the freezing time is 6 to 10 hours, the thawing temperature is 50 to 70°C, and the thawing time is 10 to 60 minutes.

[0016] Optionally, perform cyclic freeze-thaw crosslinking, including:

[0017] The freezing-thawing process is repeated 3 to 4 times, wherein the freezing temperature is -85°C to -75°C, the freezing time is 7 to 9 hours, the thawing temperature is 60 to 70°C, and the thawing time is 15 to 35 minutes.

[0018] Optionally, the immersion treatment is carried out in an ammonium sulfate-borax solution, including:

[0019] The ammonium sulfate-borax solution is immersed in the solution for 1 to 9 hours, wherein the ammonium sulfate concentration of the ammonium sulfate-borax solution is 20 to 40 wt %, and the borax concentration is 0.8 to 1.8 wt %.

[0020] In a second aspect, the present invention provides a surface enhanced transport polyvinyl alcohol-based hydrogel, which is obtained by the above-mentioned preparation method of the surface enhanced transport polyvinyl alcohol-based hydrogel.

[0021] Optionally, the ionic conductivity of the surface enhanced transport polyvinyl alcohol-based hydrogel is 10.2-13.4 mS / cm, and the drug release efficiency is 59.1%-65.9%.

[0022] Optionally, the tensile strength of the surface enhanced transmission polyvinyl alcohol-based hydrogel is 1.36-1.77 MPa, the tensile strain is 862%-1074%, and the adhesion energy is 170.3-195.5 J / m 2 .

[0023] In summary, the present invention has at least one of the following beneficial effects:

[0024] 1. The present invention discloses a method for preparing a surface enhanced transmission polyvinyl alcohol-based hydrogel, which is prepared by using specific raw materials and preparation processes. A three-dimensional network porous structure of polyvinyl alcohol and sodium alginate interpenetrating each other is formed inside the hydrogel, and a large-aperture expanded pore structure is formed on the surface. The interpenetrating three-dimensional network porous structure makes the polyvinyl hydrogel have excellent mechanical properties, especially high tensile strength and tensile strain, and can be better stretched and deformed to adapt to the shape of the surface wound. Correspondingly, the porous structure inside the hydrogel has the characteristic of small pore size, which is 200nm to 8μm. The small-aperture porous structure can maintain the good mechanical properties of the hydrogel while making the hydrogel have There is a high drug absorption and retention capacity, and the pore expansion structure on the surface of the hydrogel has a large pore size, the pore size is 10μm to 150μm, the pore expansion structure is connected to the porous structure, and the large pore size has the function of enhancing transmission, which can promote the transmission of the drug contained in the porous structure inside the hydrogel to the connected surface pore expansion structure, so that the drug contained in the porous structure inside the hydrogel is quickly delivered and released to the surface wound, thereby promoting wound healing, and at the same time, because the surface pore expansion structure expands the contact space between the porous structure inside the hydrogel and the wound surface, the adhesion ability of the hydrogel can be greatly improved, so that the hydrogel has good adhesion stability and reliability while having excellent drug release ability. In addition, the hydrogel provided by the present invention also has excellent electrical conductivity. Under the action of the electric field, the hydrogel with conductive effect can achieve directional release of drugs, improve the therapeutic effect of drugs and reduce side effects.

[0025] 2. The method for preparing a surface enhanced transmission polyvinyl alcohol-based hydrogel provided by the present invention has the advantages of simple operation, strong controllability, easy regulation, large-scale preparation and low cost, and can be promoted on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is a scanning electron microscope photograph of the surface of the polyvinyl alcohol-based hydrogel prepared in Example 1 after freeze drying;

[0027] Figure 2 This is a comparison curve of the mechanical properties of the polyvinyl alcohol-based hydrogels prepared in Example 1, Example 2, Example 3, and Comparative Example 1;

[0028] Figure 3 This is a comparison curve of drug release performance of polyvinyl alcohol-based hydrogels prepared in Example 1, Example 2, Example 3, and Comparative Example 1;

[0029] Figure 4 This is a scanning electron microscope photograph of the surface of the polyvinyl alcohol-based hydrogel prepared in Comparative Example 1 after freeze-drying. DETAILED DESCRIPTION

[0030] The present invention provides a surface enhanced transmission polyvinyl alcohol-based hydrogel and a preparation method. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0031] Polyvinyl alcohol (PVA) is a water-soluble polymer material made of vinyl acetate by polymerization alcoholysis, with good film-forming property, biocompatibility and safe degradability, and a hydrogel with a three-dimensional cross-linked network structure formed by gelling a polyvinyl alcohol aqueous solution by a cyclic freezing-thawing method, and the preparation method is simple, non-toxic and reproducible, and sodium alginate (SA) is a sodium salt of alginic acid, which is an anionic linear polysaccharide. The double network hydrogel is synthesized with SA and PVA, which can enhance the toughness and strength of the hydrogel, and the double network hydrogel has a porous structure, which is conducive to absorbing and retaining liquid, and is easy to adsorb biomolecules / drugs / antibiotics, and is used for drug delivery and release, and a pore expansion structure is formed on the surface of the hydrogel, and the pore size of the pore expansion structure is larger than the pore size of the internal porous structure, which is conducive to promoting the transmission of drugs absorbed inside the hydrogel to the surface, promoting drug delivery and release, and maintaining the excellent mechanical properties of the double network hydrogel, and in addition, the pore expansion structure can enhance the contact between the internal network structure and the wound surface, and improve the adhesion performance. The present invention is obtained on the basis of this research.

[0032] In some embodiments of the present invention, the present invention provides a method for preparing a surface enhanced transport polyvinyl alcohol-based hydrogel, comprising the following preparation steps: preparing a polyvinyl alcohol solution, adding sodium alginate to the polyvinyl alcohol solution, stirring to completely dissolve the sodium alginate in the polyvinyl alcohol solution, preparing a mixed solution, placing the mixed solution in a mold for pre-gelation, and then performing a cyclic freeze-thaw cross-linking treatment. After completion, placing the mixed solution in an ammonium sulfate-borax solution for immersion treatment, and finally preparing a polyvinyl alcohol-based hydrogel, wherein a three-dimensional network porous structure is formed inside the polyvinyl alcohol-based hydrogel, and the pore size of the porous structure is 200nm~8μm, and the surface of the polyvinyl alcohol-based hydrogel forms a pore-expanding structure capable of enhancing transport, and the pore size of the pore-expanding structure is 10μm~150μm, and the pore-expanding structure is connected to the porous structure. Preferably, the pore size of the porous structure is 500nm to 8μm; the pore size of the expanded pore structure is 10μm to 150μm; more preferably, the pore size of the porous structure is 600nm to 8μm; the pore size of the expanded pore structure is 25μm to 150μm.

[0033] In some embodiments of the present invention, the polyvinyl alcohol solution is prepared, comprising:

[0034] The polyvinyl alcohol is added to deionized water, the mass ratio of the polyvinyl alcohol to the deionized water is 5-15:45-180, and the polyvinyl alcohol is completely dissolved in the deionized water under stirring at 50-95°C, thereby preparing the polyvinyl alcohol solution, and the stirring speed is 50-500 rpm / min. Preferably, the mass ratio of the polyvinyl alcohol to the deionized water is 8-12:70-110; preferably, the polyvinyl alcohol is completely dissolved in the deionized water under stirring at 80-95°C.

[0035] In some embodiments of the present invention, sodium alginate is added to a polyvinyl alcohol solution and stirred to completely dissolve the sodium alginate in the polyvinyl alcohol solution to prepare a mixed solution, comprising:

[0036] The sodium alginate is added to the polyvinyl alcohol solution, the mass ratio of the sodium alginate to the polyvinyl alcohol solution is 2-8:45-180, and the mixture is stirred at 50-95°C and the stirring speed is 50-500 rpm / min to prepare the mixed solution. Preferably, the mass ratio of the sodium alginate to the polyvinyl alcohol solution is 4-6:80-100; preferably, the mixture is stirred at 80-95°C.

[0037] In some embodiments of the present invention, placing the mixed solution in a mold for pre-gelling comprises:

[0038] The mixed solution is placed in a mold and allowed to stand for 0.5 to 5 hours, preferably 0.5 to 3 hours.

[0039] In some embodiments of the present invention, a cyclic freeze-thaw crosslinking process is performed, comprising:

[0040] The freezing-thawing process is performed for 2 to 6 cycles, wherein the freezing temperature is -90°C to -60°C, the freezing time is 6 to 10 hours, the thawing temperature is 50 to 70°C, and the thawing time is 10 to 60 minutes.

[0041] In some embodiments of the invention, cyclic freeze-thaw crosslinking is performed, comprising:

[0042] The freezing-thawing process is repeated 3 to 4 times, wherein the freezing temperature is -85°C to -75°C, the freezing time is 7 to 9 hours, the thawing temperature is 60 to 70°C, and the thawing time is 15 to 35 minutes.

[0043] In some embodiments of the present invention, the soaking treatment in an ammonium sulfate-borax solution comprises:

[0044] The mixture is immersed in the ammonium sulfate-borax solution for 1 to 9 hours, wherein the ammonium sulfate concentration of the ammonium sulfate-borax solution is 20 to 40 wt%, and the borax concentration is 0.8 to 1.8 wt%. Preferably, the ammonium sulfate concentration is 25 to 35 wt%; preferably, the borax concentration is 1.0 to 1.6 wt%.

[0045] In some embodiments of the present invention, the ionic conductivity of the surface enhanced transport polyvinyl alcohol-based hydrogel is 10.2-13.4 mS / cm, and the drug release efficiency is 59.1%-65.9%. Preferably, the ionic conductivity is 12.5-13.4 mS / cm, and the drug release efficiency is 65.2%-65.9%.

[0046] In some embodiments of the present invention, the tensile strength of the surface enhanced transmission polyvinyl alcohol-based hydrogel is 1.36-1.77 MPa, the tensile strain is 862%-1074%, and the adhesion energy is 170.3-195.5 J / m 2 Preferably, the tensile strength is 1.65-1.77 MPa, the tensile strain is 944%-1074%, and the adhesion energy is 170.3-195.5 J / m 2 .

[0047] The present invention is further described in detail below in conjunction with specific examples and comparative examples. The raw materials in the specific examples of the present invention are commercially available unless otherwise specified.

[0048] Example 1

[0049] This embodiment provides a surface enhanced transmission polyvinyl alcohol-based hydrogel and a preparation method thereof, comprising the following steps:

[0050] S1. Prepare a polyvinyl alcohol solution: weigh polyvinyl alcohol (G108396 polyvinyl alcohol, pharmaceutical grade, adhesive strength ~240g Bloom, Shanghai Aladdin Biochemical Technology Co., Ltd.) and deionized water according to the mass ratio, the mass ratio of polyvinyl alcohol to deionized water is 10 parts:90 parts, add polyvinyl alcohol to deionized water, stir for 4 hours in a 90°C water bath to completely dissolve the polyvinyl alcohol in the deionized water, and stir at a speed of 250 rpm / min to prepare a polyvinyl alcohol solution;

[0051] S2. Preparation of mixed solution: Weigh the sodium alginate powder according to the mass ratio. The mass ratio of the sodium alginate powder (S100128, Shanghai Aladdin Biochemical Technology Co., Ltd.) of this embodiment to the above-mentioned polyvinyl alcohol solution is 5 parts:90 parts. Add the sodium alginate powder to the polyvinyl alcohol solution, stir for 3 hours in a 90°C water bath to completely dissolve the sodium alginate powder in the polyvinyl alcohol solution, and stir at a speed of 250 rpm / min to prepare a mixed solution;

[0052] S3. Preparation of hydrogel: The prepared mixed solution was poured into a mold and pre-gelated for 1.5 hours, and then subjected to three cycles of freeze-thaw cross-linking treatment, with the freezing temperature being -80°C, the freezing time being 8 hours, the melting temperature being 60°C, and the melting time being 20 minutes. After completion, the mixture was immersed in an ammonium sulfate-borax solution for 6 hours, with the concentration of ammonium sulfate in the solution being 30wt%, and the concentration of borax in the solution being 1.2wt%, to finally prepare a polyvinyl alcohol-based hydrogel.

[0053] Microstructure testing:

[0054] Scanning electron microscopy (SEM) was used to characterize the microstructure of PVA-based hydrogels. Figure 1 is a scanning electron microscope image of the surface of the polyvinyl alcohol-based hydrogel finally prepared in step S3 of Example 1 after freeze drying. Figure 1 It can be seen that the interior of the polyvinyl alcohol-based hydrogel has a three-dimensional network porous structure with a pore size of 500nm~5μm. The surface of the polyvinyl alcohol-based hydrogel has an expanded pore structure for enhanced transmission with a pore size of 15μm~120μm, and the expanded pore structure is connected to the porous structure.

[0055] Mechanical properties test:

[0056] The polyvinyl alcohol-based hydrogel was subjected to a tensile test using a universal mechanical testing machine. The polyvinyl alcohol-based hydrogel finally prepared in step S3 of Example 1 was cut to prepare a tensile sample (the length, width and height of the sample were 12*4*2mm), the tensile rate was 100mm / min, and the tensile stress and strain were calculated according to the initial cross-sectional area and initial length of the test sample. The tensile stress-strain curve of the polyvinyl alcohol-based hydrogel of Example 1 was measured as follows: Figure 2 As shown, the tensile strength of the polyvinyl alcohol-based hydrogel of Example 1 was measured to be 1.65 MPa, and the tensile strain was 1074%. It can be seen that the polyvinyl alcohol-based hydrogel prepared in Example 1 has excellent mechanical properties.

[0057] Ionic conductivity test:

[0058] The conductivity of the polyvinyl alcohol-based hydrogel was tested using an electrochemical workstation. The polyvinyl alcohol-based hydrogel finally prepared in step S3 of Example 1 was cut to prepare a conductivity test sample (the length, width and height of the sample were 12*4*2mm), and the test sample was connected to the test port of the electrochemical workstation. The transmitted electrical signal can be used to calculate the ionic conductivity of the test sample. The calculation formula is: δ=L / RS, δ is the ionic conductivity; L is the length of the test sample, S is the cross-sectional area of ​​the test sample; R is the resistance. The ionic conductivity of the polyvinyl alcohol-based hydrogel of Example 1 was measured to be 12.5mS / cm. It can be seen that the polyvinyl alcohol-based hydrogel prepared in Example 1 has excellent conductive properties.

[0059] Adhesion test:

[0060] The adhesion of the polyvinyl alcohol-based hydrogel was tested using a universal mechanical testing machine. The polyvinyl alcohol-based hydrogel finally prepared in step S3 of Example 1 was cut to prepare an adhesion sample with a length and width of 70 mm×20 mm. A layer of chitosan adhesive (coating amount of 0.5 μL / mm) was evenly coated within a range of 45 mm from one end. 2 ), and then immediately covered with a frozen pig skin strip of 70mm×20mm in size (average thickness 2.8mm). After pressing for 1 hour, take it out and soak the pig skin sample in a nearly neutral phosphate buffered saline solution (PBS buffer) for 2 hours to balance its pH. The non-adhesive sides of the hydrogel and the pig skin sample were bonded to a rigid polyester film using 502 super glue. The free ends of the rigid polyester film that bonded the hydrogel and the pig skin were clamped with a clamp for peeling. The peeling rate was 24mm / min, and the force and displacement during the peeling process were recorded. The adhesion energy is defined as the work done to peel off the adhered material per unit area, and its calculation formula is: E is the adhesion energy, F and x are the force and displacement in the peeling test, respectively, L is the maximum displacement when the hydrogel is completely separated from the pig skin, and S is the bonding area (45 mm×20 mm) coated with the chitosan adhesive. The adhesion energy of the polyvinyl alcohol-based hydrogel of Example 1 was measured to be 195.5 J / m 2 It can be seen that the polyvinyl alcohol-based hydrogel prepared in Example 1 has excellent adhesion properties.

[0061] Drug Release Testing:

[0062] 2 mg of the antibacterial drug ciprofloxacin was fully dissolved in 20 mL of deionized water, and then the polyvinyl alcohol-based hydrogel sample (the size of the sample was 5 cm*10 cm) finally prepared in step S3 of Example 1 was immersed in the ciprofloxacin solution. After the polyvinyl alcohol-based hydrogel sample completely absorbed the solution, it was placed in a dialysis bag (MW: 3500) and 7 mL of a phosphate buffer solution with a pH of 7.4 was added. The dialysis bag was placed in a conical flask containing 50 mL of a phosphate buffer solution and kept at a constant temperature of 37° C. (frequency was 100 rpm). Samples were taken at 10, 30, 40, 80, 90, 150 and 160 min and the absorbance was measured. The cumulative drug release was calculated using the calculation formula A=ε*c*l, where A is the absorbance, ε is the molar absorption coefficient, c is the concentration of the solute in the solution (mol / L), and l is the thickness of the solution (cm). Figure 3 As shown, the drug release efficiency of the polyvinyl alcohol-based hydrogel of Example 1 was measured to be 62.5% after 160 minutes. It can be seen that the polyvinyl alcohol-based hydrogel prepared in Example 1 has excellent drug release ability.

[0063] Example 2

[0064] This embodiment provides a preparation of a polyvinyl alcohol-based hydrogel, comprising the following steps:

[0065] S1. Prepare a polyvinyl alcohol solution: weigh polyvinyl alcohol (G108396 polyvinyl alcohol, pharmaceutical grade, adhesive strength ~240g Bloom, Shanghai Aladdin Biochemical Technology Co., Ltd.) and deionized water according to the mass ratio, the mass ratio of polyvinyl alcohol to deionized water is 10 parts:90 parts, add polyvinyl alcohol to deionized water, stir for 4 hours in a 90°C water bath to completely dissolve the polyvinyl alcohol in the deionized water, and stir at a speed of 250 rpm / min to prepare a polyvinyl alcohol solution;

[0066] S2. Preparation of mixed solution: Weigh the sodium alginate powder according to the mass ratio. The mass ratio of the sodium alginate powder (S100128, Shanghai Aladdin Biochemical Technology Co., Ltd.) of this embodiment to the above-mentioned polyvinyl alcohol solution is 5 parts:90 parts. Add the sodium alginate powder to the polyvinyl alcohol solution, stir for 3 hours in a 90°C water bath to completely dissolve the sodium alginate powder in the polyvinyl alcohol solution, and stir at a speed of 250 rpm / min to prepare a mixed solution;

[0067] S3. Preparation of hydrogel: The mixed solution was poured into a mold for pre-gelation for 1.5 hours, and then subjected to three cycles of freeze-thaw cross-linking treatment, with the freezing temperature being -80°C, the freezing time being 8 hours, the melting temperature being 70°C, and the melting time being 20 minutes. After completion, the mixture was immersed in an ammonium sulfate-borax solution for 6 hours, with the concentration of ammonium sulfate in the solution being 30wt%, and the concentration of borax in the solution being 1.2wt%.

[0068] The polyvinyl alcohol-based hydrogel finally prepared in step S3 of Example 2 was tested using the same characterization test method as in Example 1. It was found that the polyvinyl alcohol-based hydrogel finally prepared in step S3 of Example 2 had the same microstructure as the polyvinyl alcohol-based hydrogel prepared in Example 1, with a three-dimensional network porous structure inside and an expanded pore structure for enhanced transmission on the surface. The pore size of the porous structure was 600nm to 8μm, the pore size of the expanded pore structure was 25μm to 150μm, and the expanded pore structure was connected to the porous structure. The tensile strength of the polyvinyl alcohol-based hydrogel in Example 2 was found to be 1.77MPa, the tensile strain was 944%, the ionic conductivity was 13.4mS / cm, and the adhesion energy was 170.3J / m 2 , the drug release efficiency in 160 min was 65.9%. It can be seen that the polyvinyl alcohol-based hydrogel prepared in Example 2 has excellent mechanical properties, ion conductivity, adhesion and drug release properties.

[0069] Example 3

[0070] This embodiment provides a preparation of a polyvinyl alcohol-based hydrogel, comprising the following steps:

[0071] S1. Prepare a polyvinyl alcohol solution: weigh polyvinyl alcohol (G108396 polyvinyl alcohol, pharmaceutical grade, adhesive strength ~240g Bloom, Shanghai Aladdin Biochemical Technology Co., Ltd.) and deionized water according to the mass ratio, the mass ratio of polyvinyl alcohol to deionized water is 10 parts:90 parts, add polyvinyl alcohol to deionized water, stir for 4 hours in a 90°C water bath to completely dissolve the polyvinyl alcohol in the deionized water, and stir at a speed of 250 rpm / min to prepare a polyvinyl alcohol solution;

[0072] S2. Preparation of mixed solution: Weigh the sodium alginate powder according to the mass ratio. The mass ratio of the sodium alginate powder (S100128, Shanghai Aladdin Biochemical Technology Co., Ltd.) of this embodiment to the above-mentioned polyvinyl alcohol solution is 5 parts:90 parts. Add the sodium alginate powder to the polyvinyl alcohol solution, stir for 3 hours in a 90°C water bath to completely dissolve the sodium alginate powder in the polyvinyl alcohol solution, and stir at a speed of 250 rpm / min to prepare a mixed solution;

[0073] S3. Preparation of hydrogel: The mixed solution was poured into a mold for pre-gelation for 1.5 hours, and then subjected to three cycles of freeze-thaw cross-linking treatment, with the freezing temperature being -80°C, the freezing time being 8 hours, the melting temperature being 50°C, and the melting time being 20 minutes. After completion, the mixture was immersed in an ammonium sulfate-borax solution for 6 hours, with the concentration of ammonium sulfate in the solution being 30wt%, and the concentration of borax in the solution being 1.2wt%.

[0074] The polyvinyl alcohol-based hydrogel finally prepared in step S3 of Example 3 was tested using the same characterization test method as in Example 1. It was found that the polyvinyl alcohol-based hydrogel finally prepared in step S3 of Example 3 had the same microstructure as the polyvinyl alcohol-based hydrogel prepared in Example 1, with a three-dimensional network porous structure inside and an expanded pore structure for enhanced transmission on the surface. The pore size of the porous structure was 200nm to 3μm, the pore size of the expanded pore structure was 10μm to 75μm, and the expanded pore structure was connected to the porous structure. The tensile strength of the polyvinyl alcohol-based hydrogel in Example 3 was found to be 1.36MPa, the tensile strain was 862%, the ionic conductivity was 10.2mS / cm, and the adhesion energy was 180.5J / m 2 , the drug release efficiency in 160 min was 59.1%. It can be seen that the polyvinyl alcohol-based hydrogel prepared in Example 3 has excellent mechanical properties, ion conductivity, adhesion and drug release properties.

[0075] Comparative Example 1

[0076] This comparative example provides a preparation method of a polyvinyl alcohol hydrogel, comprising the following steps:

[0077] S1. Prepare a polyvinyl alcohol solution: weigh polyvinyl alcohol (G108396 polyvinyl alcohol, pharmaceutical grade, adhesive strength ~240g Bloom, Shanghai Aladdin Biochemical Technology Co., Ltd.) and deionized water according to the mass ratio, the mass ratio of polyvinyl alcohol to deionized water is 10 parts:90 parts, add polyvinyl alcohol to deionized water, stir for 4 hours in a 90°C water bath to completely dissolve the polyvinyl alcohol in the deionized water, and stir at a speed of 250 rpm / min to prepare a polyvinyl alcohol solution;

[0078] S2. Preparation of mixed solution: Weigh the sodium alginate powder according to the mass ratio. The mass ratio of the sodium alginate powder (S100128, Shanghai Aladdin Biochemical Technology Co., Ltd.) of this embodiment to the above-mentioned polyvinyl alcohol solution is 5 parts:90 parts. Add the sodium alginate powder to the polyvinyl alcohol solution, stir for 3 hours in a 90°C water bath to completely dissolve the sodium alginate powder in the polyvinyl alcohol solution, and stir at a speed of 250 rpm / min to prepare a mixed solution;

[0079] S3. Preparation of hydrogel: The mixed solution was poured into a mold for pre-gelation for 1.5 hours, and then subjected to three cycles of freeze-thaw cross-linking treatment, with the freezing temperature being -80°C, the freezing time being 8 hours, the melting temperature being 20°C, and the melting time being 6 hours. After completion, the mixture was immersed in an ammonium sulfate-borax solution for 6 hours, with the concentration of ammonium sulfate in the solution being 30wt%, and the concentration of borax in the solution being 1.2wt%.

[0080] The polyvinyl alcohol-based hydrogel finally prepared in step S3 of comparative example 1 was tested using the same characterization test method as in example 1. Figure 4 This is a scanning electron microscope image of the surface of the polyvinyl alcohol-based hydrogel prepared in Comparative Example 1 after freeze drying. Figure 4 It can be seen that the surface of the polyvinyl alcohol-based hydrogel prepared in Comparative Example 1 is basically non-porous. The tensile strength of the polyvinyl alcohol-based hydrogel prepared in Comparative Example 1 was measured to be 1.86 MPa, the tensile strain was 602%, the ionic conductivity was 6.6 mS / cm, and the adhesion energy was 120.2 J / m 2 , the drug release efficiency in 160 min was 38.3%. It can be seen that the mechanical properties, conductive properties, adhesion properties and drug release properties of the polyvinyl alcohol-based hydrogel prepared in Comparative Example 1 are significantly inferior to those in Example 1.

[0081] It should be understood that the application of the present invention is not limited to the above examples. For those skilled in the art, it is possible to make improvements or changes based on the above description, and all these improvements and changes should fall within the scope of protection of the claims attached to this application. In addition, unless the steps are specifically described or must occur in sequence, the order of the above steps is not limited to the above list and can be changed or rearranged according to the required design.

Claims

1. A method for preparing a surface enhanced transport polyvinyl alcohol-based hydrogel, characterized in that: The invention comprises the following preparation steps: preparing a polyvinyl alcohol solution, adding sodium alginate into the polyvinyl alcohol solution, stirring to make the sodium alginate completely dissolved in the polyvinyl alcohol solution, preparing a mixed solution, placing the mixed solution in a mold for pre-gelation, and then performing a cyclic freezing-thawing cross-linking treatment. After the pre-gelation, the mixed solution is placed in an ammonium sulfate-borax solution for immersion treatment, and finally preparing a polyvinyl alcohol-based hydrogel, wherein a three-dimensional network porous structure is formed inside the polyvinyl alcohol-based hydrogel, and the pore size of the porous structure is 200nm-8μm; and a pore expansion structure capable of enhancing transmission is formed on the surface of the polyvinyl alcohol-based hydrogel, and the pore size of the pore expansion structure is 10μm-150μm, and the pore expansion structure is connected with the porous structure.

2. The method for preparing the surface enhanced transmission polyvinyl alcohol-based hydrogel according to claim 1, characterized in that: A polyvinyl alcohol solution is prepared, comprising: The polyvinyl alcohol is added into deionized water, the mass ratio of the polyvinyl alcohol to deionized water is 5-15:45-180, and the polyvinyl alcohol is completely dissolved in the deionized water by stirring at 50-95° C., so as to prepare the polyvinyl alcohol solution, and the stirring speed is 50-500 rpm / min.

3. The method for preparing the surface enhanced transmission polyvinyl alcohol-based hydrogel according to claim 1, characterized in that: Sodium alginate is added to the polyvinyl alcohol solution, and stirred to completely dissolve the sodium alginate in the polyvinyl alcohol solution to prepare a mixed solution, comprising: The sodium alginate is added to the polyvinyl alcohol solution, the mass ratio of the sodium alginate to the polyvinyl alcohol solution is 2-8:45-180, and the mixture is stirred at 50-95° C. and the stirring speed is 50-500 rpm / min to prepare the mixed solution.

4. The method for preparing the surface enhanced transmission polyvinyl alcohol-based hydrogel according to claim 1, characterized in that: The mixed solution is placed in a mold for pre-gelling, comprising: The mixed solution is placed in a mold and allowed to stand for 0.5 to 5 hours.

5. The method for preparing the surface enhanced transmission polyvinyl alcohol-based hydrogel according to claim 1, characterized in that: Perform a cyclic freeze-thaw crosslinking process including: The freezing-thawing process is performed for 2 to 6 cycles, wherein the freezing temperature is -90°C to -60°C, the freezing time is 6 to 10 hours, the thawing temperature is 50 to 70°C, and the thawing time is 10 to 60 minutes.

6. The method for preparing the surface enhanced transmission polyvinyl alcohol-based hydrogel according to claim 5, characterized in that: Perform cyclic freeze-thaw crosslinking including: The freezing-thawing process is repeated 3 to 4 times, wherein the freezing temperature is -85°C to -75°C, the freezing time is 7 to 9 hours, the thawing temperature is 60 to 70°C, and the thawing time is 15 to 35 minutes.

7. The method for preparing the surface enhanced transport polyvinyl alcohol-based hydrogel according to any one of claims 1 to 6, characterized in that: Soaking in an ammonium sulfate-borax solution, including: The ammonium sulfate-borax solution is immersed in the solution for 1 to 9 hours, wherein the ammonium sulfate concentration of the ammonium sulfate-borax solution is 20 to 40 wt %, and the borax concentration is 0.8 to 1.8 wt %.

8. A surface enhanced transport polyvinyl alcohol-based hydrogel obtained by the preparation method of the surface enhanced transport polyvinyl alcohol-based hydrogel according to any one of claims 1 to 7. 9 . The surface-enhanced transport polyvinyl alcohol-based hydrogel according to claim 8 , wherein the ionic conductivity of the surface-enhanced transport polyvinyl alcohol-based hydrogel is 10.2 to 13.4 mS / cm, and the drug release efficiency is 59.1% to 65.9%.

10. The surface-enhanced transport polyvinyl alcohol-based hydrogel according to claim 8 or 9, wherein the surface-enhanced transport polyvinyl alcohol-based hydrogel has a tensile strength of 1.36-1.77 MPa, a tensile strain of 862%-1074%, and an adhesion energy of 170.3-195.5 J / m 2 .

Citation Information

Patent Citations

  • A method for preparing a sponge-like macroporous polyvinyl alcohol hydrogel

    CN108409988B

  • Super-macroporous hydrogel as well as preparation method and application thereof

    CN116120619A